Use of bee honey as alternative medicine in protein energy deficiency - R. Heru Prasetyo; Willy Sandhika; Djoni Susanto (Syiah Kuala University, 2013)
The protein energy deficiency cause intestinal villus atrophy and epithel mucous damage. The effect of bee honey on histostructure of intestine was studied in the experimental mice as model of proteinenergy deficiency. The use bee honey in protein-energy deficiency shown to improve intestinal villus atrophy and epithel damage. In conclusion that bee honey can use as alternative medicine in protein energydeficiency